2018
DOI: 10.7596/taksad.v7i2.1511
|View full text |Cite
|
Sign up to set email alerts
|

Sağlık Bilimleri Fakültesi Öğrencilerinin Sağlık Okuryazarlığı Düzeylerinin İncelenmesi / Examining the Health Literacy Levels of Health Sciences Faculty Students

Abstract: This study aims to examine the health literacy levels of health sciences faculty students. This descriptive and cross-sectional study was carried out between April 07 and June 1, 2017, with the students of Karabük University Health Sciences Faculty, who accepted to participate in the study (n = 300). The research data was collected using a survey form questioning participants' socio-demographic characteristics, and the "Turkish Health Literacy Scale 32 (THLS-32)". The chi-square, Mann Whitney U and Kruskal Wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 8 publications
2
12
0
5
Order By: Relevance
“…Although few studies have been done in the literature, similar findings have been reported in our study (19,20). Since the habit of reading books is generally related to the desire to learn and the desire to research, apart from reading adventure or romance novels, the desire to read, learn and research in daily life may also form the basis of health-related teachings and may be related to the high level of health literacy.…”
Section: Discussionsupporting
confidence: 89%
“…Although few studies have been done in the literature, similar findings have been reported in our study (19,20). Since the habit of reading books is generally related to the desire to learn and the desire to research, apart from reading adventure or romance novels, the desire to read, learn and research in daily life may also form the basis of health-related teachings and may be related to the high level of health literacy.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the absence of a statistically significant difference between gender groups in health literacy scores is similar to the results of the studies of Akalın et al (2021), Gün et al (2021), Uskun et al (2021), Değerli and Nezihe (2018) measuring health literacy. On the other hand, studies reveal that health literacy differs by gender (Deniz, 2020;Yılmaz Güven et al, 2018). The fact that health literacy, which contains literacy skills in its essence, does not differ by the gender variable can be attributed to the fact that the literacy rates of women and men are close to each other in developed and developing countries and the abundance of official and unofficial information channels that increase health knowledge of individuals.…”
Section: Conclusion/discussion and Recommendationsmentioning
confidence: 99%
“…Examining the sources used by students to access health-related information, it was determined that 48% reported the Internet, 29.7% reported health workers, and 16.7% reported family members and friends in the top 3. [14]…”
Section: Discussionmentioning
confidence: 99%
“…Üstün et al [18] found this mean as 30.10 in their study with pharmacy students. Yilmaz et al [14] found this score as 29.48 with the students of the Faculty of Health Sciences. In the studies conducted with nursing students during the pandemic process, it is stated that the average score obtained from the E-SYO scale is high.…”
Section: Discussionmentioning
confidence: 99%